Fusion energy using avalanche increased boron reactions for block-ignition by ultrahigh power picosecond laser pulses. (14th July 2015) - Hora, Heinrich; Korn, Georg; Giuffrida, Lorenzo; Margarone, Daniele; Picciotto, Antonino; Krasa, Josef; Jungwirth, Karel; Ullschmied, Jiri; Lalousis, Paraskevas; Eliezer, Shalom; Miley, George H.; Moustaizis, Stavros; et al.
Abstract: Exceptionally high reaction gains of hydrogen protons measured with the boron isotope 11 are compared with other fusion reactions. This is leading to the conclusion that secondary avalanche reactions are happening and confirming the results of high-gain, neutron-free, clean, safe, low-cost, and long-term available energy. The essential basis is the unusual non-thermal block-ignition scheme with picosecond laser pulses of extremely high powers above the petawatt range.